Molecular dynamics simulations of the effect of dislocations on the thermal conductivity of iron - Sun, Yandong; Zhou, Yanguang; Han, Jian; Hu, Ming; Xu, Ben; Liu, Wei (Journal of applied physics, 2020)
Phonons contribute an appreciable proportion of the thermal conductivity of iron-based structural materials used in the nuclear industry. The decrease in thermal conductivity caused by defects such as dislocations will decrease the efficiency of nuclear reactors or lead to melting failure under transient heat flow. However, the phonon–dislocation scattering rate in iron is unknown, and the details of the scattering process have not been well studied. In this paper, the effect of dislocations on lattice thermal conductivity in pure iron is studied using molecular dynamics simulations. The temperature distribution in the neighborhood of the dislocation, the spectral heat flux, and the frequency-dependent phonon mean free paths are obtained. From a comparison with the results for a perfect crystal, we find that the dislocation can significantly decrease the lattice thermal conductivity. By using an average phonon group velocity, the phonon–dislocation scattering rate under a given dislocation density is obtained from the phonon mean free paths. Moreover, eigenmode analysis of a dislocation dipole model indicates that the phonons have a certain degree of localization, which reduces their ability to transport heat. Our study reveals the details of the phonon–dislocation scattering process and may help to interpret the reduced thermal conductivity caused by the dislocations that are generated during the service lives of iron-based structural materials.